LINGUISTIC LANDSCAPE STUDY IN TAMAN SAFARI BOGOR (PANOPTICON: Journal of English Studies, 2022)
This study aims to analyze the linguistic landscape in Taman Safari Bogor tourist attractions. To analyze the researcher based on the findings found by Landry and Bourhis (1997). There are two problem formulations in this research, the first is the diversity of languages used in the linguistic landscape and the function of the linguistic landscape. This study uses a qualitative method. Qualitative methods are used by the writer to explain and interpret various kinds of signs, language and also the results of observations. The writer got 205 signs collected from observations in the outdoor and indoor areas of Taman Safari Bogor. The writer conducted interviews to find out the reasons for showing written signs at Taman Safari Bogor in various languages. The writer found several types of language used in the linguistic landscape such as monolingual, bilingual, and multilingual. The writer also found that there are 4 languages used such as Indonesian, English, Arabic, and Chinese. All signs are installed in the outdoor and indoor areas of Taman Safari Bogor as warnings and prohibitions, directions, promotions, and building names. Indonesian – English is dominant at Taman Safari Bogor. The reasons for displaying multiple languages are; educating local communities in foreign languages and facilitating information for overseas visitors.Keywords: linguistic landscape, sign, tourist attractions.